ANALYSIS OF TEACHERS' OBSTACLES IN THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM AT SD NEGERI 2 MEUREUDU PIDIE JAYA - Shavira, Nadia; Yamin, M.; Nurmasyitah, Nurmasyitah (Universitas Syiah Kuala, 2025)
Renewing the education curriculum needs to be carried out in order to improve the quality of education in Indonesia and create quality Human Resources (HR) that are able to compete with other countries in line with current developments. The independent learning curriculum is a policy that has been designed by the government with the aim of achieving significant progress in terms of the quality of education, thereby producing students and graduates who are ready to face complex future challenges. This curriculum has only been implemented in the 2021/2022 school year, and not all schools have implemented it. Therefore, there are still limited references regarding the independent learning curriculum, especially at the basic education level. The formulation of the problem in this research is